Multi-Layer PHP Source Code Protection Model Using Encoding with Integrity Hashing and Anti-Reverse Engineering - Sarmuni Sarmuni; Suhaeri Rumdani; Anna Rosdiana; Khaeroni Khaeroni; Ahmad Faturohman; Devid Sujianto; Deden Rifki (CoreID Journal, 2026)
Unprotected PHP source code is vulnerable to reverse engineering, piracy, and illegal modifications. This research aims to design and develop a multi-layer PHP source code protection model that combines obfuscation techniques, multi-layer encoding, AES-256 encryption, and hashing mechanisms with anti-tamper capabilities to maintain code confidentiality and integrity. The system is also equipped with auto-restore features and panic notification via Telegram Bot that automatically restores original files and sends security warnings when illegal changes are detected. The methodology used is Research and Development (R&D), with stages including literature review, system design, prototype development, security experiments, and performance benchmarking. The expected results show that the multi-layer model can hinder reverse engineering, accurately detect file changes, and provide rapid responses via auto-restore and Telegram notifications, significantly improving PHP source code security compared to conventional encoders. The security experiments demonstrated superior protection against deobfuscation attacks, with benchmark results showing acceptable performance overhead (an average execution-time increase of 15-20ms, a CPU load increase of 8-12%, and a memory usage increase of 5-8 MB) compared to commercial encoders.